Association of excessive screen time exposure with ocular changes leading to astigmatism in children - Mutahir Shah; Satheesh Babu Natarajan; Nafees Ahmad (PLoS ONE, 2025)
Purpose The purpose of this study was to find the relationship between excessive screen time exposure and the development of astigmatism in children. Methods A cross-sectional correlational study was conducted at tertiary care hospital, Islamabad between June 2023 to May 2024. In total, 431 patients were included in this study after informed written consent. Screen time exposure was assessed through smartphone usage history or parental reports of daily use of smart gadget(s). Tear break-up time was measured using a fluorescein strip, cobalt blue filter on a slit-lamp biomicroscope and a stopwatch. Data was analyzed using univariate and multivariate statistical tests including Spearman’s correlation and regression analyses. Results The study included 431 children (mean age: 6.70 ±  1.80 years; 55% male, 45% female). Mean screen time was 4.54 ±  1.52 hours/day. A positive correlation between screen time and the magnitude of astigmatism was observed (r = 0.33, p < 0.001). Regression analysis showed a significant relationship among screen time and astigmatism (B = 0.177, CI: 0.80-0.25). Tear break- up time (TBUT) showed a significant negative correlation with screen time (r = -0.167, p < 0.001), and reduced TBUT was linked to a higher risk of inflammatory conjunctivitis and lid thickening (B = -0.431, CI: -0.12 to -0.49, p < 0.001). The results highlighted that inflammatory conjunctivitis/lid thickness have three times greater risk of developing high astigmatism (OR =  3.31, p-value <  0.001, CI =  1.91 to 5.73) while the risk of moderate astigmatism in such cases was two times higher (2.12, p-value =  0.004, CI = 1.26-3.56). However, the effect of lid thickness on astigmatism when combining with screen time has a little effect that is not significant (p-value = 0.053). Thus, excessive screen time is an independent risk factor of causing astigmatism in children (p < 0.001). The Wilcoxon Signed Ranks Test demonstrated significant improvement in visual acuity after correction (p < 0.001). Conclusion Excessive screen time in children is significantly associated with astigmatism, tear film instability, inflammatory ocular conditions, including conjunctivitis and lid thickening. These findings suggest the need for preventive strategies, such as reducing screen time and encouraging regular eye examinations, to protect children’s ocular health.